Use of Force and Firearms
This interactive CD-ROM program, Use of Force and Firearms, has been designed as a training tool for instructors at police academies, acting as a supplement to existing training programs on this subject. The focus of the program is not on the technical aspects but on international laws and in particular on psychological and tactical aspects of use of force and firearms by law enforcement officers. Produced by COLPI (Constitutional and Legal Policy Institute)